COVID-19 vaccine development from the perspective of cancer patients - Yang He; Yi Ding; Bo Cao; Yi Huang; Xiao Wang (Taylor & Francis Group, 2021)
Currently, many companies around the world are actively developing COVID-19 vaccines. Fourteen vaccines with reliable safety and effectiveness are being successfully distributed to the public. However, there is no specific clinical trial data of the vaccines currently on the market on cancer patients at various stages, so the safety and effectiveness on cancer patients is unknown. This mini-review aims to discuss the impact of COVID-19 on cancer patients, and the urgent need of COVID-19 vaccines for cancer patients. In this review, we described the current status of the COVID-19 vaccine usages in cancer patients, as well as discussed potential problems in the use of vaccine. In addition, we included an original survey of the acceptance of the COVID-19 vaccines in 209 cancer patients and their family members. COVID-19 vaccine can provide cancer patients with social and medical benefits; therefore, clinical trials of vaccines on cancer patients are in great need.